Environmental Disclosure and Cost of Equity Capital of Public Listed Firms in Malaysia - Mohd Waliuddin, Mohd Razali; Chin, Pui Mun; Nordiana, Ahmad Nordin; Irma Yazreen, Md Yusoff; Dyg Haszelinna, Abg Ali (hrmars, 2023)
Disclosure of environmental information in Malaysia is still at a minimal level due to no clear rules and regulations for sustainability reporting which lead to information asymmetry for investors. The purpose of this study is to examine the relationship between environmental disclosure and cost equity capital (COC) firms listed on Bursa Malaysia. The sample data were collected from the annual report and Eikon database. The regression result in this study showed environmental disclosure negative relationship with COC based on 171 firm observations in 2016. This study proved environmental disclosure reduces cost equity capital by reducing information asymmetry and firm risk. For control variables, firm size is a negative relationship with COC while leverage positive relationship with cost equity capital.